STUDENTS' PERCEPTIONS OF USING DROPS APPLICATION IN ENGLISH VOCABULARY LEARNING - Siregar, Fatimah Azzahra; Dalimunte, Ahmad Amin (MUDABBIR Journal Research and Education Studies, 2025)
This study aims to explore students’ perceptions towards the use of Drops application in learning English vocabulary. Using a descriptive qualitative approach, data was obtained through semi-structured interviews with ten students majoring in Islamic Education in Medan who have used Drops application independently. The results showed that most students had positive experiences using Drops, mainly due to its visual, interactive and gamification features that enhance motivation as well as memorization. However, some challenges were also identified, such as limited context of vocabulary use, lack of personalization of materials, and mismatch of content with academic needs. The study concludes that while Drops is effective as an additional learning tool, integration into a more targeted and contextualized formal learning system is needed to make vocabulary learning more meaningful and applicable.